PENGARUH PENAMBAHAN Cr(OH)3 DAN Fe(OH)2 DALAM PEWARNA GLASIR TERHADAP MODULUS PATAH DAN DAYA SERAP BAHAN - Syarifah Aini; Noni Retno Afrianti (Universitas Muhammadiyah Jakarta, 2018)
Heavy metal waste is B3 waste that has hazardous and environmentally damaging effect, such as electroplating industry waste which produces Cr(OH)3 and Fe(OH)2 wastes. The purpose of this research is to use the waste as a mixture of glaze and to know how much the effect of Cr(OH)3 and Fe(OH)2 addition in glaze dye to the fracture modulus and the absorption capacity of the material. The materials were mashed and sieved with a size of 200 mesh, then the three materials were mixed with homogeneous which have 15% leucite, 15% lime, 70% borax composition, then suspended with water until homogeneous. Afterward, added Fe(OH)2 (comparison mix of dye as much as 3%-7% weight of glaze). The experiment was repeated by adding Cr(OH)3, then a mixture of Fe(OH)2 and Cr(OH)3. The suspension result is poured onto the test tile and be spread evenly, then inserted into the muffle, heated to 900oC for 2 hours and cooled. After that, analyzed the fracture modulus and absorption capacity of the test tile. The result of this study; first, the addition of 6% Fe(OH)2 optimize the brown color. Second, the addition of 7% Cr(OH)3 optimize the green color. Last, the addition of 3% mixture of Fe(OH)2 and Cr(OH)3 optimize yellowish green color. From the research data it can be concluded that the more metal oxides are added, the greater the fracture modulus, and the smaller the absorption.